Peran Orang Tua Dalam Menumbuhkan Minat Membaca Pada Anak Kelas II MIN Di Medan - Ramadani, Rizkia; Rustam, Rustam; Siregar, Lailatun Nur Kamalia (Faidatuna, 2024)
This research is entitled "The Role of Parents in Increasing Interest in Reading in Class II MIN Children in Medan". The aim of this research is to find out: (1) what is the interest in reading of class II elementary school students in MIN 5 Medan City, and (2) what is the role of parents in fostering children's interest in reading. This research uses a qualitative descriptive method where researchers collect data in both written and oral form from related informants. The data sources used are primary and secondary data sources. In the data collection process, researchers used 3 data collection techniques, namely observation, interviews, and documentation. The data analysis techniques used are by collecting data, reducing data, presenting data and drawing conclusions. The results of the research data reveal that the role of parents in cultivating children's interest in reading has a very important role, namely by explaining: (1) Interest in reading in class II children in MIN 5 Medan City can be said to have grown quite well because of the role of parents who help them in cultivating an interest in reading. This can be seen from students who feel happy about reading books, getting reading facilities that suit their needs, parents who create reading activities at home, and children's interest in reading. (2) The role of parents in cultivating interest in reading in class II children in Medan is by setting aside some of their time, becoming facilitators, encouraging children, providing study guides, and observing children's reading development.